The Role Of Business Diversification, Education And Development Activities On Business Performance Of Construction Companies Listed In Indonesian Stock Exchange - Jessi Charina Sembiring; Hendayani, Nenden; Rina Apriliani; Teguh Prakoso; Firman Dera (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The aim of this research is to analyze the development of companies in the capital market, especially in the accounting aspect. The companies in this study consist of a large number of subsidiaries, associated companies, and multi-group companies. This is an applied study that uses developments in accounting doctrine, particularly those that influence balance sheet analysis, comparison of financial statements over time, and ratios. The analysis results indicate an increase in stock prices, followed by a general decline the following year, likely due to changes in the economic cycle. Regarding the debt situation, there has been a significant increase. Despite this, increases continued, reaching figures that would be difficult to maintain in the future. The following year, the figure decreased due to the crisis and the disinvestment process mentioned earlier. From this analysis, it appears that the construction group experienced significant challenges in managing their debt and assets over the period, which is reflected in their share price movements, turnover, and results. The composition and variations of the group's balance sheet showed major changes during the period, mainly due to the expansion of lines of activity that required large investments in permanent structures. This situation is unsustainable and requires significant disinvestment. This shows that the capital and financial management of these groups play a very important role in maintaining the stability and growth of their companies. Additionally, we must carefully make investment decisions and manage debt to avoid creating unwanted risks in the future.